(untitled) (Research, Society and Development, 2022)
The teaching process is flexible, for the transmission of knowledge to the student, one of the strategies stands out the collaborative methodology: Inverted Classroom (SAI), where it provides didactic content before the class, reserving time in the classroom to remedy deficiencies, in order to improve the discussion, with greater use of the time to ask questions, debate, creating greater interest in the discipline, improving performance in their grades, motivation by students, improvement in the acquisition of knowledge. For the training of a medical student, it is necessary to mobilize knowledge, attitudes and skills, in order to improve medical practice, realistic simulators were created imitating reality, providing a controlled environment for this student with instant educational feedback, in order to increase confidence, psychomotor skill, anxiety, knowledge, critical thinking, together with the aim of preparing for a real situation. Objective. explore the perception of medical students at the time of building knowledge about medical skills after experiencing the environment of the Flipped Classroom. Materials and methods. A qualitative study of an applied nature, qualitative, exploratory in understanding will be carried out, the sample will be 70 students of the fourth term in the discipline of medical skills. The fully practical classes will be held in the Medical Skills laboratory, prior to the classes, the theoretical material will be available through video classes, and didactic content to be studied before the class, and this knowledge will be applied to each other and simulated dummy Expected Results. Could the flipped classroom increase awareness in the construction of knowledge in the teaching process.